2006
DOI: 10.1177/10105395060180030401
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of hyperlipidemia in Bangkok school children

Abstract: As a preliminary study, we determined the serum lipid profiles among primary school children from four Bangkok schools and identified the risk factors and their association with child lipid profiles. We conducted a cross-sectional study using fasting blood samples and food frequency questionnaires. Overall, there were 40% that had hypercholesterolemia with total cholesterol (TC) at > or = 200 mg/dl and high low density lipoprotein cholesterol (LDL-C) at > or = 130 mg/dl. Overall, 5.4% had high triglyceride (TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…The high prevalence of overweight/obesity among school-aged children in this study might be due to less physical activity and higher consumption of more unhealthy, high-fat foods, sweetened beverages and salty snacks and less milk, fruits and vegetables than recommended [2,3,26]. Various studies have shown that dietary intake, physical activity and self-discipline are major factors influencing obesity and high blood pressure [1-3,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The high prevalence of overweight/obesity among school-aged children in this study might be due to less physical activity and higher consumption of more unhealthy, high-fat foods, sweetened beverages and salty snacks and less milk, fruits and vegetables than recommended [2,3,26]. Various studies have shown that dietary intake, physical activity and self-discipline are major factors influencing obesity and high blood pressure [1-3,27].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that dietary intake, physical activity and self-discipline are major factors influencing obesity and high blood pressure [1-3,27]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term health consequences of obesity include type 2 diabetes, cardiovascular disease, hypertension, hyperlipidemia, certain forms of cancer, as well as respiratory and skin problems [6,7]. Obesity in school children was influenced by society, economic conditions, environmental changes, the family's eating habits and child rearing practices[8], leading to unhealthy eating behavior [7] and a sedentary life style characterized by increased television viewing and a lack of physical exercise [9]. It has been reported that poor self-control and low self-discipline are the most important for eating in response to external food stimuli [10,11] leading to obesity.…”
Section: Introductionmentioning
confidence: 99%